Feasibility of emergency department point-of-care ultrasound for rib fracture diagnosis in minor thoracic injury. Issue 3 (17th October 2016) - Lalande, Élizabeth; Guimont, Chantal; Émond, Marcel; Parent, Marc Charles; Topping, Claude; Kuimi, Brice Lionel Batomen; Boucher, Valérie; Le Sage, Natalie
ABSTRACT: Objectives: The main objective of this study was to evaluate the feasibility of emergency department (ED) point-of-care ultrasound (PoCUS) for rib fracture diagnosis in patients with minor thoracic injury (mTI). Secondary objectives were to 1) evaluate patients' pain during the PoCUS procedure, 2) identify the limitations of the use of PoCUS technique, and 3) compare the diagnosis obtained with PoCUS to radiography results. Methods: Adult patients who presented with clinical suspicion of rib fractures after mTI were included. All patients underwent PoCUS performed by emergency physicians (EPs) prior to a rib view X-ray. A visual analogue scale (VAS) ranging from 0 to 100 was used to ascertain feasibility, patients' pain and clinicians' degree of certitude. Feasibility was defined as a score of more than 50 on the VAS. We documented the radiologists' interpretation of rib view X-ray. Radiologists were blinded to the PoCUS results. Results: Ninety-six patients were included. A majority (65%) of EPs concluded that the PoCUS technique to diagnose rib fracture was feasible (VAS score > 50). Median score for feasibility was 63. Median score was 31 (Interquartile range [IQR] 5–57) for patients' pain related to the PoCUS. The main limiting factor of the PoCUS technique was pain during patient examination (15%). Conclusion: PoCUS examination appears to be a feasible technique for a rib fracture diagnosis in the ED. RÉSUMÉ: Objectifs: L'objectif principal de cette étude consistait à évaluer la faisabilité de l'échographie ciblée au département d'urgence (ÉDU) pour le diagnostic des fractures de côtes chez les patients ayant subi un traumatisme thoracique mineur (TTm). Les objectifs secondaires étaient les suivants : 1) évaluer la douleur au cours de la procédure de l'ÉDU, 2) identifier les limites de la technique de l'ÉDU dans ce contexte et 3) comparer le diagnostic obtenu avec l'ÉDU aux résultats de la radiographie. Méthodes: Des patients adultes avec suspicion clinique de fractures de côtes suite à un TTm ont été recrutés prospectivement et l'ÉDU a été effectuée par les médecins d'urgence avant la radiographie. Une échelle visuelle analogue (EVA) graduée de 0 à 100 a été utilisée afin d'évaluer la faisabilité de la technique, la douleur des patients et le degré de certitude des cliniciens. La faisabilité a été définie comme un score de plus de 50 sur l'EVA. Les radiographies ont été interprétées par des radiologistes à l'aveugle des résultats de l'ÉDU. Résultats: Quatre-vingt-seize patients ont été inclus. Une majorité (65%) des médecins d'urgence a conclu que la technique de l'ÉDU pour diagnostiquer les fractures de côte était faisable (score EVA>50). Le score médian de faisabilité était de 63. Le score médian de la douleur des patients était de 31 (intervalle interquartile (IQR) 5-57). Le principal facteur limitant décrit par les médecins était la douleur lors de l'examen (15%). Conclusions: L'échographie ciblée au département d'urgence semble être une technique applicable pour le diagnostic de fractures de côtes.